Women's empowerment and emancipation through entrepreneurship: extending Professor Alistair Anderson's contributions. Issue 7 (8th August 2022) - Ibáñez, María José; Guerrero, Maribel
ABSTRACT: This study represents a tribute to Professor Alistair Anderson's contributions to female entrepreneurship research. Although female entrepreneurship was only one research line in Professor Anderson's extensive academic career, his contributions are embedded in the most contemporary discussion about the most vulnerable female entrepreneurs. Inspired by Professor Anderson's research on the influence of entrepreneurship on the empowerment and emancipation of female entrepreneurs in the Global South countries, our study provides empirical evidence about how entrepreneurship affects women's empowerment and emancipation compared with other occupational choices (e.g. full-time employees and homemakers). Our study includes provocative implications/discussion about gender dynamics, and the most vulnerable women enrolled in entrepreneurial activities.